Hidden female urinary incontinence in urology and obstetrics and gynecology outpatient clinics in Turkey: what are the determinants of bothersome urinary incontinence and help-seeking behavior? - TARCAN, TUFAN (SPRINGER LONDON LTD, 2007)
The purpose of this study was to assess the prevalence of female urinary incontinence (UI) and risk factors of bothersomeness and help-seeking behavior of hidden female UI in urology and obstetrics and gynecology outpatient clinics. This multicentric and cross-sectional study was conducted as a part of the Turkish Overactive Bladder Study. Female patients (n=5,565) who were referred with complaints other than UI and overactive bladder symptoms were surveyed using the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) with supplementation of five more questions. The crude prevalence of UI was found to be 35.7%. The prevalence of frequent and severe incontinence was 8.2 and 6.8%, respectively. The mean age of incontinent patients was significantly higher (p < 0.001). The prevalence of stress, urge, and mixed UI was 39.8, 24.8, and 28.9%, respectively. More than half (53%) of incontinent patients were not bothered by UI, and only 12% of incontinent patients had previously sought medical help for their problem. Frequency, severity, and type of UI were independent factors for predicting bothersome UI, while only bothersomeness increased help-seeking behavior. The ICIQ-SF score of 8 has been found to be the best cutoff value to delineate the bothersome UI. Although the crude prevalence of female UI was found to be high, bothersome UI was not so common. The majority of incontinent female patients did not seek medical help. Frequency, severity, and mixed type of UI were found to be the determinants of bothersome UI for which the ICIQ-SF cutoff score of 8 was obtained.
Keywords: epidemiology; female; help seeking; urinary incontinence; EPIDEMIOLOGIC SURVEY; PREVALENCE; WOMEN; STANDARDIZATION; QUESTIONNAIRE; TERMINOLOGY; COMMUNITY; IMPACT